Looking for blazars in a sample of unidentified high-energy emitting Fermi sources: preliminary results - Marchesini, Ezequiel Joaquín (2015)
It is expected that a large fraction of the unidentified sources detected at γ-rays are blazars. Through cross–correlation between the positions of unidentified objects from the 1FHL Fermi catalogue of γ-ray sources and the ROSAT, XMM Slew and Swift/XRT catalogues of X–ray objects, a sample of 38 associations was found with less than 10 arcsec of positional error. One third of them has recently been classified; the remainder, though believed to belong to the blazar class, has not yet been identified. Therefore, we aim at studying the optical spectra of the counterparts of these unidentified sources in order to find their redshifts and to analyse their nature and main spectral features. We present here our preliminary results from optical spectroscopic observations at the 3.58m Telescopio Nazionale Galileo (TNG) for 7 of them.